2020
DOI: 10.3390/app10207079
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Oxygen Forecasting in Aquaculture: A Hybrid Model Approach

Abstract: Dissolved oxygen (DO) concentration is a vital parameter that indicates water quality. We present here DO short term forecasting using time series analysis on data collected from an aquaculture pond. This can provide the basis of data support for an early warning system, for an improved management of the aquaculture farm. The conventional forecasting approaches are commonly characterized by low accuracy and poor generalization problems. In this article, we present a novel hybrid DO concentration forecasting me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…The acceptable value of σ is typically within the range of 0.2 and 0.3 [1]. In practice, the sifting process is terminated automatically once the computed σ value lies within the acceptable range of 0.2 and 0.3.…”
Section: Eemd Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptable value of σ is typically within the range of 0.2 and 0.3 [1]. In practice, the sifting process is terminated automatically once the computed σ value lies within the acceptable range of 0.2 and 0.3.…”
Section: Eemd Methodsmentioning
confidence: 99%
“…One aspect is monitoring the fluctuations of water quality parameters, e.g., dissolved oxygen, pH, temperature, salinity, etc., that are known to adversely affect the aquaculture environment. In some cases, even slight variations above or below the normal, optimal water quality parameter conditions may lead to physiological stress on the aquatic life, which can impact their feeding, breeding and increases susceptibility to diseases [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The EEMD technique and deep learning LSTM NN were merged to form the chlorophylla hybrid prediction model. A detailed implementation processes of the applied EEMD technique is shown in full in [13]. The LSTM deep learning NN approach is described in full detail in Section 3.1.…”
Section: Proposed Modelmentioning
confidence: 99%
“…However, the challenge with traditional numerical methods, LSSVR, and neural networks such as RBFNN and BPNN is the inherent weakness of the long-term dependency problem. Research has shown that deep learning long short-term memory (LSTM) neural networks can overcome the above-mentioned weakness and can provide efficient applicability and reliability for water quality parameter prediction [13,14]. Additionally, combining the ensemble empirical mode decomposition (EEMD) method with deep learning LSTM neural network has demonstrated clear advantages over traditional LSTM neural networks in terms of improved water quality parameter prediction accuracy in the aquaculture environment [13].…”
Section: Introductionmentioning
confidence: 99%
“…decreasing when temperature increases and may be represented with a single or a combination of exponential functions. This has been established for pure water, ponds, aquacultures, marine environments [Millero et al, 2002;Geng and Duan, 2010;Karbowiak et al, 2010;Valderrama et al, 2016;Eze and Ajmal, 2020], but also for physiological aqueous solutions of NaCl and human plasma [Christoforides et al, 1969;Christmas and Bassingthwaighte, 2017]. Christoforides et al [1969] measured the concentration of oxygen X O2 [mL(gas)/L(fluid)] dissolved in human plasma at different temperatures T (°C) in the interval from 10 to 60° C, at standard atmospheric pressure.…”
Section: Dario Camuffomentioning
confidence: 99%